ANALISIS KUALITAS SISTEM INFORMASI INTELEGEN NEGARA MENGGUNAKAN FRAMEWORK COBIT 5 PADA BIN SUMATERA SELATAN - Angga Madona; Tata Sutabri (Jurnal Komunikasi, 2024)
Information technology has significantly influenced and changed the way businesses are managed and monitored today. Information technology has been used by many companies as a solution in facing and winning competition. In line with this, a Cobit 5 framework is needed with the APE 1-4 programming language to ensure that the information technology implemented requires companies to maximize profits, information technology risks are managed appropriately and used responsibly. In order to achieve these goals, careful and optimal planning, implementation, support, supervision and evaluation are required. By applying analysis of the quality of the employee satisfaction management information system in using the existing system at BIN South Sumatra Intelligence, it can provide solutions in updating and improving the quality of the existing system